Evaluasi Program Gerakan Sayang Perempuan Ojek Online Dalam Meningkatkan perlindungan dan Pemberdayaan Perempuan di Kota Surabaya - Emmanuela Wiji Marlia (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
. In the city of Surabaya, a large number of female online ojek drivers face problems such as prejudice, non-disclosure, and dangerous working conditions. While there are laws against violence, the quantity of sexual incidents suggests a lack of consistency in their application. By providing skills development, legal support, and psychological counseling, the Gerakan Sayang Perempuan Ojek Online (GASPOL) initiative seeks to strengthen safety and self-determination for female online ojek drivers. This research uses descriptive qualitative methodology and collects data through observation, documentation, and interviews. William N. Dunn developed evaluation criteria for the GASPOL program, which include effectiveness, efficiency, adequacy, alignment, responsiveness, and accuracy. The GASPOL program met the needs of the participants, was efficient in using resources, and effective in improving the safety and competence of women drivers. In addition, the program was sensitive to feedback from participants and successfully distributed benefits equitably. Despite the success of the program, there are still challenges that influence public opinion, such as gender bias. To increase acceptance of women drivers, more outreach and education is needed. Keywords: , , , , (Times New Roman, size 10 font Italic)